PENGENDALIAN KUALITAS PRODUK PC SPUN PILE DENGAN MENGGUNAKAN METODE SIX SIGMA PADA PT. JAYA BETON INDONESIA SURABAYA - Alfianto, Renaldy Dimas (Universitas Negeri Surabaya, 2023)
Six Sigma is a method used by companies in determining the possibility of zero defect product defects in the production process. The six sigma method uses calculations to analyze the level of defects in production and makes an opportunity to analyze defect factors in PC spun pile products at PT. Jaya Beton Indonesia. The purpose of this study was to determine the value of six sigma on the quality of PC Spun pile to reduce the level of product defect and failure factors. The method used in this study uses the six sigma method with stages of conducting interviews, checking product reject reports, and analysis in the field. The results of PC spun pile quality control at PT. Jaya Beton Indonesia shows a six sigma value of 3.46. Types of product defects include crack defects (68.42%), less thickness (10.53%), visible seamline (7.89%), non-conforming joints (7.89%), perforated (5.26%) with factors causing product defects, namely from labor factors, work methods, and machines. Proposals to reduce product defects include rechecking each workmanship, increasing supervision in each process, adding supervision at the tension or iron withdrawal stage, carrying out processes in accordance with the applicable WI, and checking tools regularly